Peningkatan Pemahaman Mahasiswa Tentang Makanan Cepat Saji Terhadap Kesehatan Di Universitas Almarisah Madani - Fitri Adriani; Lilis Suryani; Musfira Dahlan; Ningsi Angraeni; Miranty S (JCS, 2025)
Fast food or fast food is also known to the public as junk food. Based on research results, 93.5% of students are obese and there is a relationship between irregular eating patterns and eating instant food too often and the incidence of obesity. This can be caused by a lack of awareness that consuming fast food has a negative impact on body health. Adolescents' knowledge of fast food consumption is one of the causes of health problems in adolescents as a result of consuming fast food. So it is necessary to carry out community service activities by providing education to students which aims to increase students' understanding of fast food on health. This community service activity was carried out at Almarisah Madani University DIII Midwifery Study Program in January 2025. This activity uses an educational method with several stages, preparation, implementation and evaluation. The target is 20 students. This activity shows that education about fast food on health has increased knowledge among students from 40% who had good knowledge before the service and increased to 80% after the activity was carried out.